Pathways Toward High-energy Li-sulfur Batteries, Identified via Multi-reaction Chemical Modeling. Issue 1 (18th January 2022) - Korff, Daniel; Colclasure, Andrew M.; Ha, Yeyoung; Smith, Kandler A.; DeCaluwe, Steven C.
Abstract : Here we present a 1D model of a Li-Sulfur battery with physically derived geometric parameters and thermodynamically consistent electrochemical kinetics. The approach enables straightforward comparison of proposed Li-S mechanisms and provides insights into the influence of polysulfide intermediates on battery discharge. Comparing predictions from multiple mechanisms demonstrates the need for both lithiated and non-lithiated polysulfide species, and highlights the challenge of developing parameter estimates for complex electrochemical mechanisms. The model is also used to explore cathode design strategies. Discharge performance and polysulfide concentrations for electrolyte/sulfur ratios in the range 2–4 μ L mg −1 identifies trade-offs that limit battery energy and power density, and highlights the risk of polysulfide precipitation. New cathode and electrolyte approaches must limit polysulfide concentrations in the electrolyte, both to unlock better rate capabilities in Li-S technology and to prevent capacity fade due to polysulfide precipitation.